1996
DOI: 10.1007/bf02648175
|View full text |Cite
|
Sign up to set email alerts
|

Computer-based compensation of adult reading disabilities

Abstract: We studied the use of computer readers, and especially their speech synthesis component, as a compensatory tool for adults with dyslexia. We first explored the enhancement of reading skills in a group of college students and working adults. Their unaided reading was very slow, and most participants in the study could sustain reading for only short periods. Although their timed comprehension was poor, their untimed comprehension was above average. The computer reader enhanced the reading rate and comprehension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 11 publications
2
35
0
Order By: Relevance
“…a subsequent study of adults with reading disabilities, Elkind, Black, and Murray (1996) showed enhanced performance in reading speed and endurance when using OCR as compared to reading unaided. Similarly, Higgins and Raskind (1997) in a study of postsecondary students with LD found that severely disabled readers improved reading comprehension scores when using OCR.…”
Section: Journal Of Special Education Technologymentioning
confidence: 92%
“…a subsequent study of adults with reading disabilities, Elkind, Black, and Murray (1996) showed enhanced performance in reading speed and endurance when using OCR as compared to reading unaided. Similarly, Higgins and Raskind (1997) in a study of postsecondary students with LD found that severely disabled readers improved reading comprehension scores when using OCR.…”
Section: Journal Of Special Education Technologymentioning
confidence: 92%
“…Elkind (1998) and Elkind, Black, and Murray (1996), working with postsecondary students, found that the changes in reading rate and comprehension test scores observed when students used assistive reading software were inversely related to the students' unassisted performance: that is, students who read slowest or with poorest comprehension benefited the most. Higgins and Raskind (1997) obtained a similar result.…”
Section: Introductionmentioning
confidence: 96%
“…His results were equivocal in that the text-to-speech system improved comprehension of only a few of the passages that his students read. Students with reading disabilities also have reported that reading was less tiring and less stressful when they used assistive reading software and that they could double or triple the time that they could sustain reading (Elkind, et al, 1996). This paper reports on an exploratory study of the effect of assistive reading software on students who have a primary diagnosis of attention disorder 2 rather than a reading disability.…”
Section: Introductionmentioning
confidence: 96%
“…Existing data suggest that for many students, the comprehension of material is improved when passages are read by the technology compared to a no-treatment control (Elkind, Black, & Murray, 1996;Higgins & Raskind, 1997). An interesting finding of these college studies is that comprehension gains are not uniformly present and when participant data are aggregated, changes in comprehension are not statistically present.…”
Section: Introductionmentioning
confidence: 97%